Embracing diversity: how ‘pride and prejudice’ shaped my cultural identity / Aileen Farida Mohd Adam - Mohd Adam, Aileen Farida (Academy of Language Studies, 2023)
At the age of 18, I left Sarawak for Kuala Lumpur expecting a new and exciting chapter, full of possibilities. However, I quickly encountered an unforeseen difficulty in KL: a sense of not quite belonging in either the Malay or Chinese culture. Back in Sarawak, cultural tolerance was the norm, and my dual heritage had never been a problem. This personal journey of unexpected cultural minefield and discoveries draws a parallel with Jane Austen’s classic: “Pride and Prejudice”. I was put in the same position as Elizabeth Bennet, the spirited protagonist of the novel, where I struggled with preconceived cultural assumptions that challenged my understanding of the world as I knew it. My experiences at a university with a rich diversity of culture taught me the complexity of cultural identity, much like the scenes in “Pride and Prejudice” where social gatherings and conversations become the springboard for discovery and growth. My mixed parentage had granted me a unique identity, but it seemed like I didn't completely belong to either culture. This sense of displacement made me anxious and befuddled, leaving me longing for the familiar embrace of home.